2006
DOI: 10.1002/path.1939
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression ofHOX genes in neoplastic and non-neoplastic human astrocytes

Abstract: HOX genes are a large family of regulatory genes implicated in the control of developmental processes. HOX genes are involved in malignant transformation and progression of different types of tumour. Despite intensive efforts to delineate the expression profiles of HOX genes in other cell types, nothing is known regarding the global expression profile of these genes in normal human astrocytes and astrocytomas. The present study has analysed the expression profile of the 39 class I HOX genes in normal human ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…The effect of BA treatment on invasive tendency in U-118 and U-138 glioma cell lines was also studied. The results from RT-PCR analysis revealed expression of 26/39 HOX genes in NHAs in agreement with an earlier study (28). HOX A6, A7, A9, A13, B13, C6, C8, C10, D1, D4, D9, D10, and D13 were all silent in the NHA cell line.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The effect of BA treatment on invasive tendency in U-118 and U-138 glioma cell lines was also studied. The results from RT-PCR analysis revealed expression of 26/39 HOX genes in NHAs in agreement with an earlier study (28). HOX A6, A7, A9, A13, B13, C6, C8, C10, D1, D4, D9, D10, and D13 were all silent in the NHA cell line.…”
Section: Discussionsupporting
confidence: 79%
“…Previously, it was reported that HOXD genes were expressed in neoplastic astrocytes (21) and pediatric low-grade gliomas (22). However, little is known about the function of HOXD genes, particularly in gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…Direct detection of the PCR product was monitored by measuring the increase in fluorescence caused by the binding of SYBR Green to dsDNA as described previously. 30 …”
Section: Real-time Pcrmentioning
confidence: 99%
“…19 During normal morphogenesis, HOXD13 is involved in the determination of the terminal digestive and urogenital tracts. [20][21][22] HOXD13 deregulation has been further detected in different tumor types, such as breast cancer, melanoma, cervical cancer and atrocytomas, [23][24][25][26] and in the neuro-endocrine differentiation of human advanced prostate cancers. 27 Here, to immunohistochemically detect the expression of HOXD13 homeoprotein in normal tissues and its potential deregulation along the evolution of specific tumor types, we utilized tissue microarrays (TMAs) including >4,000 different normal tissue and cancer sample types from 79 different tumor categories.…”
mentioning
confidence: 99%